Depression, anxiety, and telomere length in young adults: Evidence from the National Health and Nutrition Examination Survey - Needham, Belinda (Mol Psychiatry, 2014)
Telomere length has been hypothesized to be a marker of cumulative exposure to stress, and stress is an established cause of depression and anxiety disorders. The goal of this study was to examine the relationship between depression, anxiety and telomere length, and to assess whether this relationship is moderated by race/ethnicity, gender, and/or antidepressant use. Data were from the National Health and Nutrition Examination Survey, 1999–2002. Telomere length was assessed using the quantitative polymerase chain reaction method of telomere length relative to standard reference DNA. Past year major depression (MD), generalized anxiety disorder (GAD) and panic disorder (PD), as well as depressed affect and anxious affect, were assessed using the Composite International Diagnostic Inventory (N=1,290). Multiple linear regression was used to assess the relationship between depression and anxiety disorders and telomere length. Among women, those with GAD or PD had shorter telomeres than those with no anxious affect (β: −0.07, p<0.01), but there was no relationship among men (β: 0.08, p>0.05). Among respondents currently taking an antidepressant, those with MD had shorter telomeres than those without (β: −.26, p<.05), but there was no association between MD and telomere length among those not using antidepressants (β: −.00, p>.05). Neither depressive nor anxiety disorders were directly associated with telomere length in young adults. There was suggestive evidence that pharmacologically-treated MD is associated with shorter telomere length, likely reflecting the more severe nature of MD that has come to clinical attention.